A second coffin for Chernobyl. - Riebeck, H.
Plans are being finalized to encase the Chernobyl Reactor 4 in the worlds largest movable structure, a 20000-ton steel shell so large that indoor rain is a serious design consideration. The shell will serve two purposes, to keep [radioactive] dust in and rain out. The structure is meant to cover the old sarcophagus for the next 100 years, while over 200 tons of uranium, nearly a ton of plutonium, and other radioactive debris are extracted and prepared for more permanent disposal. The approximately 113-meter-tall shell will be equipped with four ceiling cranes that will help workers break down the reactor and remove radioactive materials. The steel structure will be built piecemeal off-site, then slid into place on greased steel plates.
Keywords: 113 m; 20000 ton; Chernobyl Reactor 4.; Ceiling cranes; Greased steel plates; Movable structure; Radioactive materials removal; Steel shell; Steel structure